2018
DOI: 10.1111/jcmm.13977
|View full text |Cite
|
Sign up to set email alerts
|

Immunometabolism features of metabolic deregulation and cancer

Abstract: Immunometabolism is a branch dealing at the interface of immune functionalities and metabolic regulations. Considered as a bidirectional trafficking, metabolic contents and their precursors bring a considerable change in immune cells signal transductions which as a result affect the metabolic organs and states as an implication. Lipid metabolic ingredients form a major chunk of daily diet and have a proven contribution in immune cells induction, which then undergo metabolic pathway shuffling inside their ownse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 108 publications
(156 reference statements)
0
22
0
Order By: Relevance
“…Nearly one‐half of postmenopausal women develop osteoporosis, but menopause also increases incidence of other comorbidities including coronary artery disease, certain cancers, chronic obstructive pulmonary disease, stroke, and dementia . It is tempting to speculate that the proinflammatory T cells produced by E 2 loss also contribute to the pathogenesis of these conditions because all these conditions are known to be caused by both chronic inflammation and metabolic syndrome . In conclusion, our studies establish a new regulatory circuit between E 2 , the immune system, and the skeletal system.…”
Section: Discussionmentioning
confidence: 69%
“…Nearly one‐half of postmenopausal women develop osteoporosis, but menopause also increases incidence of other comorbidities including coronary artery disease, certain cancers, chronic obstructive pulmonary disease, stroke, and dementia . It is tempting to speculate that the proinflammatory T cells produced by E 2 loss also contribute to the pathogenesis of these conditions because all these conditions are known to be caused by both chronic inflammation and metabolic syndrome . In conclusion, our studies establish a new regulatory circuit between E 2 , the immune system, and the skeletal system.…”
Section: Discussionmentioning
confidence: 69%
“…Immunometabolic research revealed that the activity of the immune system is not possible without the activation of the appropriate metabolic pathways (Wang, Ping, et al, 2019). From a physiological perspective, immunity uses anabolic pathways at the cost of growth and reproduction (Wang, Luan, et al, 2019 (Scharsack et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, not all effects of leptin are beneficial, as recent evidence suggests that leptin can impair CD8 T cell immunity via a STAT3-dependent signaling pathway that culminates in elevated PD-1 expression and suppression of T cell proliferation, leading to functional exhaustion. 68 With obesity, adipocytes fail to properly store fatty acids, resulting in increased free fatty acids in the plasma of humans and mice. 18 However, many cell types, including T lymphocytes, have a limited capacity to process lipids, so chronically elevated intracellular concentrations of these substances can induce lipotoxicity, which manifests as cellular damage, dysfunction, and eventually death (reviewed in reference 17 ).…”
Section: The Complex Effects Of Host Obesity On T Cell Effector Funmentioning
confidence: 99%
“…As cytotoxic CD8 T cells have been described as existing in synonymous pro‐inflammatory, IFNγ+Tc1, and anti‐inflammatory, IL‐4+Tc2, subsets, it is possible that obesity‐associated leptin may also skew CD8 effector T cell differentiation toward a pro‐inflammatory profile, although this idea remains to be tested. However, not all effects of leptin are beneficial, as recent evidence suggests that leptin can impair CD8 T cell immunity via a STAT3‐dependent signaling pathway that culminates in elevated PD‐1 expression and suppression of T cell proliferation, leading to functional exhaustion …”
Section: Obesity‐associated Alterations In Cd8 T Cell Function and Mementioning
confidence: 99%